KAUM MUDA DALAM HIDUP MENGGEREJA DI LINGKUNGAN ST. FILIPUS PAROKI ROH KUDUS SURABAYA - Prisdiana, Theresia Widya; Ardijanto, Don Bosco Karnan (CREDENDUM: Jurnal Pendidikan Agama, 2024)
Basic christian community of St. Philip at the Holy Spirit Parish in Surabaya inhabited by many catholic young people so called catholic young people (Orang Muda Katolik or OMK). Most of the OMK members consist of the students or workers. The busyness of studying and working resulting in many of OMK’s members are not actively involved in the church activities. Most of them rarely and reluctantly participate in the Church activities. They spend most of their holidays and free time with their own friends, and they pay less attention to the Church’s activities. The research was conducted with the aim of identifying factors (motivation) which are supporting the involvement of OMK in the Church activities, especially in St. Philip basic christian community. OMK's involvement in the church activities is rooted in the sacrament of Baptism. Through this sacrament, OMK is called to take part in the five missions of the Church in the world so called Liturgia, Kerygma, Koinonia, Diakonia, Martyria. This research used qualitative methods. Data collection was carried out by using individual interview techniques. There were 8 members of OMK interviewed for the study. All of those OMK’s members live in St. Philip’s basic christian community.The results of the research pointed out that the majority of OMK’s members in the basic christian community were less actively involved in church’s activities. This was due to several factors, including OMK’s activities being too boring, busyness of working and studying, and the lack of support of their parents. The results of research also pointed out there was a small number of OMK’s members in the christian community were actively involved in church activities due to the internal and external motivation.